Gram scale preparation of clozapine N-oxide (CNO), a synthetic small molecule actuator for muscarinic acetylcholine DREADDs - Phillip L. van der Peet; Christian Gunawan; Alaa Abdul-Ridha; Sherie Ma; Daniel J. Scott; Andrew L. Gundlach; Ross A.D. Bathgate; Jonathan M. White; Spencer J. Williams (MethodsX, 2018)
Chemogenetics uses engineered proteins that are controlled by small molecule actuators, allowing in vivo functional studies of proteins with temporal and dose control, and include Designer Receptors Exclusively Activated by Designer Drugs (DREADDs). One major class of DREADDs are mutated muscarinic receptors that are unresponsive to acetylcholine, and are activated by administration of clozapine N-oxide (CNO). However, CNO is available in only small amounts and large scale studies involving animals and multiple cohorts are prohibitively expensive for many investigators. The precursor, clozapine, is also expensive when purchased from specialist suppliers. Here we report: • A simple extraction method of clozapine from commercial tablets; • A simple preparation of CNO from clozapine, and for the first time its single-crystal X-ray structure; and • That the CNO prepared by this method specifically activates the DREADD receptor hM3Dq in vivo.This method provides large quantities of CNO suitable for large-scale DREADD applications that is identical to commercial material. Method name: Preparation and application of clozapine N-oxide (CNO), Keywords: G-protein-coupled receptor (GPCR), Chemical-genetics, Chemical synthesis